A Contribution by Multidimensional Methods to Choosing Descriptive Data for EEG by Spectral Analysis - Chavance, M.; Samson-Dollfus, Dominique (Methods of Information in Medicine, 1976)
One of the main difficulties in automatic analysis of EEG tracings is the reduction of data; spectral analysis allows only a partial reduction. Principal component analysis is used to determine amongst a group of quantitative variables those which best describe a given sample of power spectra. The tracings come from normal children (10 to 12 years of age) recorded on four leads (fronto-central right and left, centro-occipital right and left) in five experimental situations (resting with eyes closed, during five minutes of hyperventilation, resting with eyes open, and during simple arithmetic and vocabulary tests, eyes closed). It is shown that four variables are enough to describe the spectra.
Keywords: EEG; Power Spectra; Multivariate Analysis